Antagonistic Effect of a Cytoplasmic Domain on the Basal Activity of Polymodal Potassium Channels - Soussia, Ismail Ben; Choveau, Frank S.; Blin, Sandy; Kim, Eun-Jin; Feliciangeli, Sylvain; Chatelain, Franck C.; Kang, Dawon; Bichet, Delphine; Lesage, Florian (Frontiers in Molecular Neuroscience, 2018)
TREK/TRAAK channels are polymodal K+ channels that convert very diverse stimuli, including bioactive lipids, mechanical stretch and temperature, into electrical signals. The nature of the structural changes that regulate their activity remains an open question. Here, we show that a cytoplasmic domain (the proximal C-ter domain, pCt) exerts antagonistic effects in TREK1 and TRAAK. In basal conditions, pCt favours activity in TREK1 whereas it impairs TRAAK activity. Using the conformation-dependent binding of fluoxetine, we show that TREK1 and TRAAK conformations at rest are different, and under the influence of pCt. Finally, we show that depleting PIP2 in live cells has a more pronounced inhibitory effect on TREK1 than on TRAAK. This differential regulation of TREK1 and TRAAK is related to a previously unrecognized PIP2-binding site (R329, R330, R331) present within TREK1 pCt, but not in TRAAK pCt. Collectively, these new data point out pCt as a major regulatory domain of these channels and suggest that the binding of PIP2 to the pCt of TREK1 results in the stabilization of the conductive conformation in basal conditions.